Optimizing Digital Marketing to Support MSME Promotion and Marketing Activities - Fernanda, Eryansya Alga; Hariyanto, Didik (Universitas Muhammadiyah Sidoarjo, 2024)
In an ever-evolving digital era, Micro, Small, and Medium Enterprises (MSMEs) in Indonesia face challenges in optimally leveraging digital marketing potential. Despite approximately 77% of the population having internet access, many MSMEs still rely on conventional methods, limiting their market reach and visibility. This study aims to explore the importance of optimizing digital marketing for MSMEs, particularly in Jedongcangkring Village, to support promotional and marketing activities. A qualitative approach was employed, utilizing in-depth interviews to gather data. The findings indicate that the implementation of digital marketing strategies, such as the use of social media platforms and data analysis, can enhance campaign effectiveness, expand market share, and strengthen MSMEs' presence in the digital business ecosystem. Furthermore, understanding the Technology Acceptance Model (TAM) is crucial in encouraging the adoption of new technologies. Recommendations from this research include enhancing education and support for MSMEs in implementing digital marketing strategies, enabling them to compete more effectively in an increasingly interconnected digital marketplace.